Ritual dynamics and religious change in the Roman Empire: proceedings of the Eighth Workshop of the International Network Impact of Empire (Heidelberg, July 5 - 7, 2007) - Hekster, Olivier; Schmidt-Hofner, Sebastian; Witschel, Christian (Impact of Empire, 2009)
Introduction. The dynamics of rituals in the Roman Empire / Angelos Chaniotis -- Ritualising the empire. Du pontifex maximus à l'élu de Dieu : l'Empereur et les sacra (Ier s. av. n. e.-Ve s. de n. e.) / Stéphane Benoist -- From conquest to pax Romana : the signa recepta and the end of the Triumphal Fasti in 19 BC / Ida Östenberg -- The pompa circensis and the domus Augusta (1st-2nd c. A.D.) / Patrizia Arena -- Honouring ancestors : the dynamic of deification / Olivier Hekster -- Empire of the sun? Civic responses to the rise and fall of Sol Elagabal in the Roman Empire / Martijn Icks -- Performing civic community in the empire. Civic rituals in imperial ostia / Christer Bruun -- Das reich tanzt-- : dance in the Roman Empire and its discontents / Frits G. Naerebout -- Die Bewirtung des Volkes : Öffentliche Speisungen in der Römischen Kaiserzeit / Eftychia Stavrianopoulou -- Rituels civiques (apantèsis et acclamations) et gouverneurs en Asie Mineure à l'époque romaine / Anne-Valérie Pont -- Kommunikation durch Herrschaftszeichen : Römisches Militär und römische Amtsträger in den Provinzen / Werner Eck -- Performing religion in the empire. Found in translation : the religion of the Roman diaspora / Greg Woolf -- Women and sacrifice in the Roman Empire / Emily A. Hemelrijk -- Les repas funéraires : un témoignage d'une dynamique socio-culturelle en Afrique romaine / Arbia Hilali -- Neue Bilder für alte Rituale : die Saturn-Stelen als Kultmedien im römischen Nordafrika / Günther Schörner -- Götterbilder im römischen Griechenland : vom Tempel zum Museum? / Christoph Auffarth -- Luna/MHN ÆKANŒ : un dieu romain à Antioche (Pisidie) / Nicole Belayche -- Miniaturisierung als Schlüssel zum Verständnis römerzeitlicher ägyptischer Rituale? / Joachim Friedrich Quack